FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN - Tatang, Stefvano Christianto; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2025)
This research in the long term aims to increase knowledge in dividend policy in manufacturing companies listed on the Indonesia Stock Exchange. The increase was in the form of increased utilization as a comparison to determine dividend policies for various companies, which in this study focused on manufacturing companies. Dividend Policy which is very influential on investors to determine dividends in the place of investment. The specific purpose of this study is to find out the effect of Profitability on dividend policy, Know the influence of Firm Size on dividend policy, know the effect of Laverage on dividend policy and know the effect of Liquidity on dividend policy. By using the variables Current Ratio, Size, Return on Assets, and Debt to Equity Ratio in the Dividend Payout Ratio. The results of this study show that the Variable Laverage and Liquidity have a significant positive influence on dividend policy, and the Variable Profitability and Firm size have a significant negative influence on dividend policy.